Recent Advances in the Diagnosis and Treatment of Chronic Liver Diseases - Enomoto, Hirayuki (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Chronic liver diseases develop from a wide range of causes, including hepatitis B virus (HBV) infection, hepatitis C virus (HCV) infection, alcoholic-related liver disease, non-alcoholic fatty liver disease (NAFLD), and autoimmune liver diseases. Recent advances in molecular and cellular techniques have succeeded in providing new aspects in the diagnosis and treatment of chronic liver diseases. This book includes the state-of-the-art researches on chronic liver diseases.